ChemInform Abstract: Rhodium(III)‐Catalyzed C—C Bond Formation of Quinoline N‐Oxides at the C‐8 Position under Mild Conditions. Issue 10 (March 2015) - Jeong, Jisu; Patel, Pitambar; Hwang, Heejun; Chang, Sukbok
Abstract The Rh‐catalyzed alkylation of a variety of substituted quinoline N‐oxides with activated methylene compounds (II) and (VI) is investigated to give C‐8 substituted products selectively.